2023
DOI: 10.1186/s12943-023-01807-w
|View full text |Cite
|
Sign up to set email alerts
|

The use of RNA-based treatments in the field of cancer immunotherapy

Abstract: Over the past several decades, mRNA vaccines have evolved from a theoretical concept to a clinical reality. These vaccines offer several advantages over traditional vaccine techniques, including their high potency, rapid development, low-cost manufacturing, and safe administration. However, until recently, concerns over the instability and inefficient distribution of mRNA in vivo have limited their utility. Fortunately, recent technological advancements have mostly resolved these concerns, resulting in the dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(21 citation statements)
references
References 746 publications
0
21
0
Order By: Relevance
“…The mRNA vaccines are a potential immunotherapy solution to combat various types of cancer, prompting the immune system to destroy cancer cells by triggering a specific and enduring immune response against tumor antigens (TAs), inhibiting tumor growth ( Miao et al, 2021 ). Nevertheless, in clinical trials it has been observed that although there is a certain level of positive response from patients ( Papachristofilou et al, 2019 ), it does not seem to be a sufficiently robust response to cause tumor recession or an increase in overall survival for all the patients ( Chehelgerdi and Chehelgerdi, 2023 ), leading to termination of their production. For that reason, pharmaceutical companies ought to incorporate novel molecular tools to improve cancer mRNA vaccines, to promote good immunological responses.…”
Section: Resultsmentioning
confidence: 99%
“…The mRNA vaccines are a potential immunotherapy solution to combat various types of cancer, prompting the immune system to destroy cancer cells by triggering a specific and enduring immune response against tumor antigens (TAs), inhibiting tumor growth ( Miao et al, 2021 ). Nevertheless, in clinical trials it has been observed that although there is a certain level of positive response from patients ( Papachristofilou et al, 2019 ), it does not seem to be a sufficiently robust response to cause tumor recession or an increase in overall survival for all the patients ( Chehelgerdi and Chehelgerdi, 2023 ), leading to termination of their production. For that reason, pharmaceutical companies ought to incorporate novel molecular tools to improve cancer mRNA vaccines, to promote good immunological responses.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, cancer vaccines have received increasing attention from researchers. mRNA vaccine therapy can induce an immune response in the body and plays a role in eliminating tumor cells through the tumor microenvironment, thus prolonging the survival of patients [ 33 ]. Many studies have shown cancer vaccine efficacy and therapeutic potential for tumor treatment [ 34 – 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to infectious diseases, nucleic acids have been studied in the context of cancer research, where DNA and mRNA vaccines encoding a broad range of tumor antigens are used. Extensive reviews of nucleic acid vaccines have been conducted previously [ 55 , 56 ]. While the principles of nucleic acid vaccines for cancers and infectious diseases are similar, this review mainly focuses on infectious diseases in poultry.…”
Section: Vaccine Formulationsmentioning
confidence: 99%